Screening Echocardiography in Adults with Down Syndrome. Issue 5 (May 2023) - King, Thomas C.; Karan, Abhinav; Edwards, Linda; Jacob, Rafik
Abstract: Down syndrome is the most common chromosomal disorder in the United States, occurring in about 14.14/10, 000 births. It is associated with multiple medical anomalies, including cardiac, gastrointestinal, musculoskeletal, and genitourinary abnormalities, which increases the burden of morbidity for this patient population. Management is typically directed toward optimizing health and function throughout childhood and into adulthood; however, consensus regarding their management in adulthood is controversial. The burden of congenital cardiac diseases in children with trisomy 21 is well established, seen in more than 40% of cases. Although screening echocardiography is performed routinely within 1 month of birth, current consensus advocates for diagnostic echocardiography only in symptomatic adults with Down syndrome. Here, we advocate that screening echocardiography should be performed routinely in this patient population at all ages, particularly in late adolescence and early adulthood, because of a high percentage of residual cardiac defects and an increased risk of developing valvular and structural cardiac disease.